Nursing Students' Experiences in Consecutive Clinical Interprofessional Education in Japan: Application of the IPE in Nursing Colleges - Junko Shida; Mariko Otsuka (MDPI AG, 2022)
Aim: To document nursing students' experiences of continuous participation in a clinical interprofessional education (IPE) program with the Faculty of Pharmacy of other universities in Japan, which had been incorporated into the existing practicum program, and consider how to develop a one-shot clinical IPE program. Methods: The study participants were two nursing students from a single-department college; they were participating in a clinical IPE program-the first IPE program they had ever participated in-during an area-based practicum in Year 3. Subsequently, in Year 4, a semi-structured interview was conducted, and these interview data were qualitatively and inductively analyzed. Results: Seven categories were identified, and it was found that through continuous participation in the IPE program, there was a change from "clinical IPE is stuck at the back of their mind as a bitter experience" to "the process of clinical IPE stimulates their maturity as a nursing student" and "cultivates attitudes necessary for cooperation". Conclusion: Consecutive years of continuous clinical IPE helps students deepen their understanding of learning content by reducing the physical and mental burden of multidisciplinary cooperation and collaboration. For difficulties with regard to step-by-step IPE, it is suggested that one-shot clinical IPE can be conducted for the upper grades along with continuous reflection activities for teams and individuals.